Penerapan Model Pembelajaran Problem Based Learning Berbantuan Media Scrapbook Di Lengkapi LKS Quizizz Untuk Meningkatkan Hasil Belajar Siswa: (Implementation of the Problem-Based Learning Model Assisted by Scrapbook Media and Supplemented with Quizizz Worksheets to Improve Student Learning Outcomes) - Landu, Irvin Neli; Bano, Vidriana Oktoviana; Huda, Marleni Rosalia Ndapa (BIODIK, 2026)
This study was motivated by the low Biology learning outcomes of Grade XIIB students at SMA Kristen Payeti, attributed to the use of monotonous, teacher-centered learning models and a lack of engaging learning media. The study aimed to describe the implementation process and the improvement of student learning outcomes through the Problem-Based Learning (PBL) model, supported by scrapbook media and Quizizz worksheets. This research employed a Classroom Action Research (CAR) design conducted over two cycles. The subjects were 33 students from class XIIB at SMA Kristen Payeti. Learning outcome data were collected via cognitive tests (multiple-choice) and observations of the affective domain, specifically focusing on self-confidence, cooperation, and curiosity. Data analysis utilized descriptive quantitative methods to calculate average scores and the percentage of classical mastery. The results demonstrated a significant improvement in both cognitive and affective learning outcomes. In the pre-cycle stage, the average cognitive score was 57.57, with a classical mastery rate of only 13% (4 students) and a non-mastery rate of 87% (29 students). Following the intervention in Cycle I, the mastery rate rose to 46% (15 students). The most significant improvement occurred in Cycle II, where the mastery rate reached 90% (30 students), falling into the high category. Regarding the affective domain, the percentage of positive student attitudes was 67% in the pre-cycle (poor category), 75% in Cycle I (fair category), and rose to 82% in Cycle II (good category). Based on these findings, it can be concluded that the implementation of the PBL model, supported by scrapbook media and Quizizz worksheets, is effective in improving student learning outcomes in the Biotechnology unit. Abstrak. Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar Biologi siswa kelas XIIB SMA Kristen Payeti, yang disebabkan oleh penggunaan model pembelajaran yang masih monoton dan berpusat pada guru, serta terbatasnya penggunaan media pembelajaran yang menarik. Tujuan penelitian ini adalah untuk mendeskripsikan proses penerapan dan peningkatan hasil belajar siswa melalui model Problem Based Learning (PBL) berbantuan media Scrapbook dan LKS Quizizz. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Subjek penelitian adalah siswa kelas XIIB SMA Kristen Payeti yang berjumlah 33 orang. Data hasil belajar dikumpulkan melalui tes kognitif (pilihan ganda) dan observasi ranah afektif yang mencakup aspek percaya diri, gotong royong, dan rasa ingin tahu. Teknik analisis data dilakukan secara deskriptif kuantitatif untuk menghitung nilai rata-rata dan persentase ketuntasan klasikal. Hasil penelitian menunjukkan adanya peningkatan yang signifikan pada hasil belajar kognitif dan afektif siswa. Pada tahap pra-siklus, rata-rata nilai kognitif siswa adalah 57,57 dengan ketuntasan klasikal hanya 13% (29 siswa). Setelah penerapan tindakan pada Siklus I, persentase ketuntasan meningkat menjadi 46% (15 siswa). Peningkatan paling signifikan terjadi pada Siklus II, dimana persentase ketuntasan mencapai 90% (30 siswa) dengan kategori tinggi. Pada ranah afektif persentase sikap siswa pada pra siklus 67% (kategori kurang) pada siklus I 75% (kategori cukup) pada siklus II meningkat hingga menjadi 82% (kategori baik). Berdasarkan hasil tersebut, dapat disimpulkan bahwa penerapan model PBL berbantuan media Scrapbook dan LKS Quizizz efektif dalam meningkatkan hasil belajar siswa pada materi Bioteknologi.   This research is motivated by the low Biology learning outcomes of class XIIB students of Payeti Christian High School, which is caused by the use of monotonous and teacher-centered learning models, as well as the limited use of interesting learning media. The purpose of this study is to describe the process of implementing and improving student learning outcomes through the Problem Based Learning (PBL) model assisted by Scrapbook media and Quizizz LKS. This type of research is Classroom Action Research (CAR) which is carried out in two cycles. The subjects of the study were 33 class XIIB students of Payeti Christian High School. Learning outcome data were collected through cognitive tests (multiple choice) and affective domain observations covering aspects of self-confidence, mutual cooperation, and curiosity. Data analysis techniques were carried out descriptively quantitatively to calculate the average value and percentage of classical completion. The results showed a significant increase in students' cognitive and affective learning outcomes. In the pre-cycle stage, the average cognitive value of students was 57.57 with classical completion of only 13% (29 students). After the implementation of the action in Cycle I, the percentage of completion increased to 46% (15 students). The most significant increase occurred in Cycle II, where the percentage of completion reached 90% (30 students) with a high category. In the affective domain, the percentage of student attitudes in the pre-cycle was 66.51% (sufficient category) in cycle I 75% (less category) in cycle II increased to 82% (good category). Based on these results, it can be concluded that the implementation of the PBL model assisted by Scrapbook media and Quizizz LKS is effective in improving student learning outcomes in Biotechnology material.